Associations Between Nutritional Deficits and Physical Performance in Community-Dwelling Older Adults - Lu, Wan-Hsuan; Giudici, Kelly Virecoulon; Rolland, Yves; Guyonnet, Sophie; Mangin, Jean-François; Vellas, Bruno; de Souto Barreto, Philipe (Frontiers in Nutrition, 2021)
Background - Whether multiple nutritional deficiencies have a synergic effect on mobility loss remains unknown. This study aims to evaluate associations between multi-nutritional deficits and physical performance evolution among community-dwelling older adults. Methods - We included 386 participants from the Multidomain Alzheimer Preventive Trial (MAPT) (75.6 ± 4.5 years) not receiving omega-3 polyunsaturated fatty acid (PUFA) supplementation and who had available data on nutritional deficits. Baseline nutritional deficits were defined as: plasma 25 hydroxyvitamin D <20 ng/mL, plasma homocysteine >14 μmol/L, or erythrocyte omega-3 PUFA index ≤4.87% (lower quartile). The Short Physical Performance Battery (SPPB), gait speed and chair rise time were used to assess physical performance at baseline and after 6, 12, 24, 36, 48 and 60 months. We explored if the nutrition-physical performance associations varied according to the presence of low-grade inflammation (LGI) and brain imaging indicators. Results - Within-group comparisons showed physical function (decreased SPPB and gait speed; increased chair rise time) worsened over time, particularly in participants with ≥2 nutritional deficits; however, no between-group differences were observed when comparing individuals without deficit and those with either one or ≥2 deficits. Our exploratory analysis on nutritional deficits-LGI interactions showed that, among people ≥2 deficits, chair rise time was increased over time in participants with LGI (adjusted mean difference: 3.47; 95% CI: 1.03, 5.91; p=0.017), compared to non-LGI individuals. Conclusions - Accumulated deficits on vitamin D, homocysteine and omega-3 PUFA was not associated with physical performance evolution in older adults, but they determined declined chair rise performance in subjects with low-grade inflammation.